Variations in clinical presentation of Fallot's tetralogy in infancy. Angiographic and pathogenetic implications. - Shinebourne, E A (1975)
Striking variability has been observed in the presenting features in infancy of patients subsequently shown to have tetralogy of Fallot. Some patients presented with severe cyanosis in the neonatal period while others had a systolic murmur and cyanosis only on crying. In these latter patients cyanosis became present at rest over the subsequent months. Yet others presented with episodic attacks of unconsciousness, and a final group presented with dyspnoea and heart failure, accompanying a left-to-right shunt. Angiography demonstrates corresponding variations in the anatomy of the ventricular outflow tracts. In the severely cyanosed patients, the conus septum was deviated so as to obstruct the pulmonary outflow tract, and was best visualized in the lateral projection. In the patients with increasing cyanosis or episodic attacks of unconsciousness, the conus septum again obstructed the pulmonary infundibulum, but was obliquely orientated, not being seen clearly on either lateral or frontal projections. The episodic attacks were considered to be related to infundibular spasm, as previously shown to occur in Fallot's tetralogy. In contrast, increasing cyanosis was believed to be related to hypertrophy of infundibular musculature. In the patients with an initial left-to-right shunt, the arteries were orientated side-by-side so that the conus septum was observed in the frontal projection. Again, subsequent cyanosis was related to ventricular hypertrophy producing outflow tract obstruction. These findings are interpreted in the setting of a recent study, indicating that Fallot's tetralogy is produced by rotation of the embryonic conus together with sinistro-anterior deviation of the conus septum.